2016
DOI: 10.1093/swr/svv046
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-National Validation of the Short Employment Hope Scale (EHS-14) in the United States and South Korea

Abstract: The Short Employment Hope Scale (EHS-14) has been developed in the United States to assess an individual's level of psychological self-sufficiency-a complementary measure to the widely used economic self-sufficiency in workforce development programs. This study examined the comparability of the EHS-14 between U.S. and South Korean low-income job seeker groups. A multisample confirmatory factor analysis (CFA) and a series of invariance tests were conducted to validate EHS-14 using two independent samples. A lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…A later study found a four‐factor structure of EHS: Psychological empowerment, futuristic self‐motivation, utilisation of skills and resources, and goal orientation (Hong et al, 2014). These factors of EHS were similarly validated in a national sample of South Korean low‐income jobseekers in the government sponsored Self‐Sufficiency Program (Hong et al, 2016). However, it is the first time to have tested the measure with a North Korean refugee sample whose understanding of the translated Korean version of EHS may be different than that of the previously studied South Korean low‐income jobseekers.…”
Section: Building a New Economic Future With Employment Hopementioning
confidence: 99%
“…A later study found a four‐factor structure of EHS: Psychological empowerment, futuristic self‐motivation, utilisation of skills and resources, and goal orientation (Hong et al, 2014). These factors of EHS were similarly validated in a national sample of South Korean low‐income jobseekers in the government sponsored Self‐Sufficiency Program (Hong et al, 2016). However, it is the first time to have tested the measure with a North Korean refugee sample whose understanding of the translated Korean version of EHS may be different than that of the previously studied South Korean low‐income jobseekers.…”
Section: Building a New Economic Future With Employment Hopementioning
confidence: 99%
“…Y. P. Hong, Choi, & Polanin, 2014; P. Y. P. Hong, Polanin, & Pigott, 2012, Hong, Song, Choi, & Park, 2016) and the Perceived Employment Barrier Scale (PEBS; P. Y. P. Hong, Polanin, Key, & Choi, 2014; P.…”
Section: Psychological Self-sufficiency (Pss) Theorymentioning
confidence: 99%
“…Over the last three decades, the market-based concept of self-sufficiency in the U.S. social welfare policy has impacted welfare reforms in other countries. The SSP in South Korea is one example of U.S. policy transfer (P. Y. P. Hong et al, 2016).…”
Section: The Self-sufficiency Program (Ssp) In South Koreamentioning
confidence: 99%
See 1 more Smart Citation
“…Y. P. Hong, Polanin, et al, 2014; P. Y. P. Hong, Polanin, & Pigott, 2012; P. Y. P. Hong, Song, Choi, & Park, 2016, 2018; P.…”
mentioning
confidence: 99%